Prepositional Phrase and Its Translations Found in the Novel “Budha, a Story of Enlightenment” - Juliarta, I Made (e-Journal of Linguistics, 2021)
The novel “Budha, A Story of Englightenment” is one of popular novels with New York Times Best Selling authors. This novel tells story as an icon of peace and serenity.  The sentences with prepositional phrase and their translations from English into Indonesian are found in this novel. Therefore, the author is interested in analyzing the translation process occured in translating the source text into target text. The source text is analyzed and viewed to find out the translation of prepositional phrase. The translation is the proccess of transferring form from the first language into second language using semantic structure. This study aims at analyzing the source text and get the meaning and its translation. It is stated  that a prepositional phrase is a group of words consisting of a preposition, its object, and any words modifying the object. A prepositional phrase also modifies a verb or a noun. There are two kinds of prepositional phrases which are called adverbial phrases and adjectival phrases. There are some complex prepositional phrases. Those are as for, except for, according to, by means, on the part of, etc. This present study is intended to: (i) identify the types of lexical and syntactical forms of the English prepositional phrases found in the data source “Budha, A Story of Englightenment”, (ii) analyze the types of shifts of prepositional phrases that were applied in the translation from source text into target text in the novel “Budha, A Story of Englightenment”